2020
DOI: 10.21203/rs.3.rs-27573/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Embryonic stem cell microenvironment enhances proliferation of human retinal pigment epithelium cells by activating the PI3K signaling pathway

Abstract: Background: Retinal pigment epithelium (RPE) replacement has been proposed as an efficacious treatment for Age-related macular degeneration (AMD), which is the primary causes of vision loss in the elderly worldwide. The embryonic stem cell (ESC) microenvironment has been demonstrated to enable mature cells to gain a powerful proliferative ability and even enhance the stem/progenitor phenotype via activation of the phosphoinositide 3-kinase (PI3K) signaling pathway. As the PI3K signaling pathway plays a pivotal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The study demonstrated that the stem cell microenvironment gained a powerful proliferative ability and stem phenotype through activation of PI3K signaling pathway. In comparison to retinal pigment epithelium cells cultured alone, the cells cocultured with stem cells had a higher colony-forming efficiency with significantly upregulated PI3K pathway-related genes [66]. The inhibition of activated MAPK1 could enhance stemness maintenance in the tumor microenvironment, which suggested that phosphorylated MAPK could be a putative target for cancer treatment.…”
mentioning
confidence: 98%
“…The study demonstrated that the stem cell microenvironment gained a powerful proliferative ability and stem phenotype through activation of PI3K signaling pathway. In comparison to retinal pigment epithelium cells cultured alone, the cells cocultured with stem cells had a higher colony-forming efficiency with significantly upregulated PI3K pathway-related genes [66]. The inhibition of activated MAPK1 could enhance stemness maintenance in the tumor microenvironment, which suggested that phosphorylated MAPK could be a putative target for cancer treatment.…”
mentioning
confidence: 98%